HUBUNGAN KEKUATAN OTOT LENGAN DAN KOORDINASI MATA TANGAN DENGAN PASING BAWAH BOLA VOLI EKSTRAKURIKULER PUTRA SMAN 1 CANDIPURO - Gading Fajar; Joan Siswoyo; M.Fajril Rifaldo; Lungit Wicaksono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the relationship between arm muscle strength and hand-eye coordination to the underhand passing of volleyball at SMAN 1 Candipuro. The method used is the correlational method. The research sample consisted of 20 people. The research instruments used were push-ups, throwing and catching the ball and underhand passing of volleyball. The research hypothesis: 1) there is a relationship between arm muscle strength and underhand passing, 2) there is a relationship between hand-eye coordination and underhand passing, 3) there is a relationship between arm muscle strength and hand-eye coordination to underhand passing. The results of the study showed that: 1) there is a significant relationship between arm muscle strength and underhand passing (r count = 0.504 > r table = 0.468), 2) there is a significant relationship between hand-eye coordination and underhand passing (r count = 0.507 > r table = 0.468), 3) Simultaneously, arm muscle strength and hand-eye coordination to underhand passing (r count = 0.750 > r table = 0.468) and a contribution of 56.35%.